17β-estradiol protects sheep oviduct epithelial cells against lipopolysaccharide-induced inflammation in vitro. (November 2020) - Ge, Wenbo; Duan, Hongwei; Xiao, Longfei; Lv, Jianshu; Jiang, Yuting; Ding, Ziqiang; Hu, Junjie; Zhang, Yong; Zhao, Xingxu
Highlights: LPS induced an inflammatory response in sheep oviduct epithelial cells. E2 reversed the LPS-induced increases in pro-inflammatory cytokine levels. E2 acts through receptors ERα/β and GPR30 to activate PI3K/AKT pathway inhibited TLR4 expression, p38 MAPK and NF-κB activity. E2 can potentially be used as a treatment for salpingitis in sheep. Abstract: Estrogen has known anti-inflammatory effects, but the mechanism whereby 17β-estradiol (E2) protects oviduct sheep epithelial cells from inflammation remains unknown. In this study, we detected the E2 synthetase and E2 nuclear and membrane receptors in sheep oviducts, primarily in epithelial cells. Using lipopolysaccharide (LPS)-stimulated sheep oviduct epithelial cells as an in vitro inflammation model, we demonstrated that E2 attenuates the expression of inflammatory factors in a concentration-response manner. E2 also inhibited the LPS-stimulated phosphorylation of p38 MAPK and NF-κB p65 but did not reduce the phosphorylation of JNK and ERK 1/2. This attenuation was partially antagonized by an intracellular estrogen antagonist that was involved in genomic regulation and enhanced by a G protein-coupled estrogen receptor agonist that was involved in nongenomic cellular modulation. These results suggest that E2 has an inhibitory effect on LPS-induced oviduct epithelial cell inflammation in sheep, which is mediated by the downstream regulatory effects of estrogen receptors.